Betalain as a Food Colorant: its Sources, Chemistry and Health Benefits: Chemistry of Betalain and its Role as Food Colorant - Naseer, Sumra; Hussain, Shabbir; Abid, Amin (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2019)
Food colors are essential ingredients of modern processed foods. Betalain can be used as a natural color source for various foods due to its nutritional and safety value. This natural and water soluble dye occurs either as red-violet betacyanin or the yellow-orange betaxanthins. Betalain plays a vital role in human health due to its pharmacological activities such as antioxidant, anti-lipidemic, antimicrobial, antitumor, antiviral and anticancer potential. There are many eatable sources of betalain e.g., Opuntia stricta (cactus fig), Opuntia ficus-indica (barbary fig), Beta vulgarius (red beet), Amaranathus tricolor (Amaranath), Celosia argentea (silver cock’s comb) and Chenopodium quinoa Wild. Red beetroot provides carotenoids, glycine, betanin, saponins, betacyanin, folates, polyphenols and flavonoids. Amaranthus is an important source of vitamin C, vitamin B, soluble fiber, betacyanin and shows significant antimalarial and antimicrobial activity. Celosia argentea Linn provides carbohydrates, vitamins, dietary minerals and high amount of betalain. Chenopodium quinoa contains high content of vitamins and minerals. Betalain of Opuntia ficus-indica fruits (barbary fig) possesses strong anti-proliferative activity. Extract of prickly pear (cactus fig) pulp which contains betalain, can act as an antibiotic agent in cases of wounds, digestive and urinary tract infections and inflammations. It also has significant inhibitory effect against humanoid ovarian tumor and cervical cancer cells. Optimum pH for maximum stability of betanin lies between pH 5.5 and 5.8. Betalain stability is affected by long term exposure to oxygen/air, light in the presence of oxygen, high temperature and water activity (aw) but it is highly stable in the presence of low moisture.